T THE INFLUENCE OF TRANSPARENCY AND PUBLIC PARTICIPATION ON VILLAGE FUND MANAGEMENT IN VILLAGE GOVERNMENT - nuralvia; Kumala Putri P, Andi Sri; Ayu, Ari (Paser Institute Of Accounting and Finance, 2024)
The management of village funds should adhere to principles of transparency and give priority to the interests of the community. Nevertheless, several instances of misappropriation of village money persist in different regions of Indonesia, and the general comprehension of village fund management remains inadequate. The objective of this study is to investigate and assess the impact of transparency and community participation on the management of the Village Fund in the Panca Rijang District. This research methodology employs saturated sampling, selecting a sample of 60 individuals who participated in village meetings. The data were analyzed with the SPSS Statistics 26 software. The findings indicated that transparency had a favorable and substantial impact on the administration of village funds, as evidenced by a computed t value of 2,486 and a significance level of less than 0.05. Community participation has a strong and statistically significant impact on village fund management, as evidenced by a computed t value of 5,931 and a significance level of 0.00, which is below the threshold of 0.05. Transparency and community participation have a statistically significant and favorable impact on village fund management, as indicated by a significance level of 0.03, which is below the threshold of 0.05.